Establishment of Waqf to Alleviate Poverty Among Muslims in Oyo State South-West, Nigeria: Test of Theory of Planned Behaviour - Abdulkareem, Ibraheem Alani; Mahmud, Mohd Sadad; AbdulGaniyy, AbdulFattah; Aliu, Olanrewaju Atanda (Li Falah: Journal of Islamic Economics and Business, 2020)
Poverty is on the increase in Africa in general and specifically in Nigeria despite the numerous poverty alleviation programs of successive governments. Lamentably, most poverty alleviation initiatives have failed to produce meaningful outcomes despite billions of Naira committed to them. Nigerians and Nigeria still ranked among the poorest, with the poverty rate rising since the 1980s. Base on the theory of planned behavior, this study examines the influences of attitude, subjective norm, perceived behavioral control, Religiosity, and available information on the intention to establish Waqf in Oyo state, southwestern Nigeria. Survey data from 218 Islamic scholars revealed that all the variables, as mentioned earlier, except available data, have a significant positive influence on the intention to establish Waqf according to the respondents.  Based on the results, the study made relevant policy recommendations regarding how authority can explore Waqf's institution as a formidable alternative to government-driven poverty alleviation programs in the interest of the Nigerian Muslims and the Nigerian Muslims, the larger population cutting across different religions.